Temperament Moderates Associations Between Exposure to Stress and Children's Externalizing Problems. Issue 5 (25th February 2013) - Schermerhorn, Alice C.; Bates, John E.; Goodnight, Jackson A.; Lansford, Jennifer E.; Dodge, Kenneth A.; Pettit, Gregory S.
Abstract : The interaction between a temperament profile (four groups determined by high vs. low resistance to control [unmanageability] and unadaptability [novelty distress]) and family stress in predicting externalizing problems at school in children followed from kindergarten through eighth grade (ages 5–13) was investigated. The sample consisted of 556 families (290 boys). At Time 1 just prior to kindergarten, mothers retrospectively reported on their child's temperament during infancy. Each year, mothers reported stress and teachers reported children's externalizing problems. Temperament profile was tested as a moderator of the stress–externalizing association for various time periods. Results indicated that the combination of high resistance to control and high unadaptability strengthens the stress–externalizing association. Findings are discussed in terms of possible underlying mechanisms.